RELATIONSHIPS BETWEEN LIPID PROFILE AND COMPLETE BLOOD CELL COUNT PARAMETERS - Yevhen Dzis; Oleksandra Tomashevska; Andriy Petrukh (Acta Medica Leopoliensia)
Aim. Given that blood cells play an important role in both atherogenesis and lipid metabolism, the research aimed to assess the specifics of the relationship between the parameters of the blood lipid spectrum and the complete blood count (CBC).